Mixed methods inquiries in the assessment of development guidelines for the Geodesic Dome Visitors’ Centre at Pulau Payar - Yusof, Zeenat Begam (IIUM Press, 2013)
This chapter describes the methodology used in the in the assessment of the Federal Department of Town and Country Planning (JPBD) Island Development Guidelines and the impacts of Pulau Payar Geodesic Dome Centre on the surrounding environment of the Pulau Payar Marine Park. This research aims was to understand the extent of the implementation of the JPBD Island Development Guidelines in the physical planning of the Visitors’ Centre and the impacts of the development on the surrounding environment. This chapter explains the various methods used to obtain data regarding the assessment and the impacts of the Visitors Centre. This research applies qualitative research utilising several techniques for data collection such as semi-structured interviews, structured observation using checklist method, visual method and document analysis.